2021
DOI: 10.7717/peerj.12135
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography rather than substrate type determines bacterial colonization dynamics of marine plastics

Abstract: Since the middle of the 20th century, plastics have been incorporated into our everyday lives at an exponential rate. In recent years, the negative impacts of plastics, especially as environmental pollutants, have become evident. Marine plastic debris represents a relatively new and increasingly abundant substrate for colonization by microbial organisms, although the full functional potential of these organisms is yet to be uncovered. In the present study, we investigated plastic type and incubation location a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 104 publications
(152 reference statements)
2
13
0
Order By: Relevance
“…Biogeography is incontestably a driver of microbial diversity. Similar results were also obtained by Coons et al, 2021 who found that biogeography influences Plastisphere community structure more than substrate type. Differences in the biofilm community composition are related to different factors.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Biogeography is incontestably a driver of microbial diversity. Similar results were also obtained by Coons et al, 2021 who found that biogeography influences Plastisphere community structure more than substrate type. Differences in the biofilm community composition are related to different factors.…”
Section: Resultssupporting
confidence: 88%
“…They found diverse microbial communities, including heterotrophs, autotrophs, predators, and symbionts, which they called a 'Plastisphere'. Coons et al (2021) investigated plastic-type and incubation locations in the Atlantic and Pacific oceans, focusing on shore locations as drivers of marine bacterial community structure development on plastic via 16S rRNA gene amplicon analysis. They found that incubation location was the primary driver of the coastal Plastisphere composition.…”
Section: Introductionmentioning
confidence: 99%
“…At sea, microplastics are readily colonized by a variety of marine organisms, creating an ecosystem that is distinct from its surrounding water which is referred to as the plastisphere (Zettler et al, 2013). It was shown that the plastic microbiome composition is variable among different geographical locations (Oberbeckmann et al, 2014;Amaral-Zettler et al, 2015;Coons et al, 2021) and that it is affected by environmental factors such as salinity, water temperature, light, and nutrient availability (Amaral- Zettler et al, 2015;Oberbeckmann et al, 2018;Misic and Covazzi Harriague, 2019). Although the colonization characteristics of microbial communities on microplastics have been investigated in a variety of short-term (Oberbeckmann et al, 2014(Oberbeckmann et al, , 2016Coons et al, 2021;Zhang et al, 2022) and long-term (Pinnell and Turner, 2020) in-situ experiments, only few studies have investigated the effects of both geographical and seasonal factors in the natural environment (Dong et al, 2021;Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has explored the taxonomic composition and spatiotemporal patterns of plastic‐colonizing microorganisms in aquatic environments using microscopy and molecular biology tools (Zettler et al ., 2013 ; Amaral‐Zettler et al ., 2015 ; Oberbeckmann et al ., 2018 ; Coons et al ., 2021 ). Results from these studies have indicated that microbes inhabiting the plastisphere reflect the local environments.…”
Section: Introductionmentioning
confidence: 99%
“…Results from these studies have indicated that microbes inhabiting the plastisphere reflect the local environments. These communities appear to be highly variable in taxa dominance compared with the populations in the surrounding water, with plastic‐type having a more minor influence on the community composition (Amaral‐Zettler et al ., 2015 ; Coons et al ., 2021 ). Importantly, plastic debris has been shown to serve as a substrate for colonization and spread of opportunistic human pathogens and bacteria related to antibiotic resistance, suggesting that these pollutants could constitute a vector for horizontal gene transfer (Zettler et al ., 2013 ; Oberbeckmann et al ., 2018 ).…”
Section: Introductionmentioning
confidence: 99%